Pengembangan Fitur Bebas Bengkalai Yang Terintegrasi Dengan Tanda Tangan Digital Pada Aplikasi SIM-LAB Di Jurusan Teknik Informatika dan Komputer - Parenreng, Jumadi M; Wahyu Hidayat M; B, Muhammad Fajar (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
Digital transformation in all areas of life has reached the Metaverse era, especially in the field of education which has an impact on changing the education paradigm. This transformation is a driving force to improve the quality of education in Indonesia, Universities which are the mecca of civilization should adopt the progress of digital transformation, the Department of Informatics and Computer Engineering in this case in laboratory management requires an integrated and well-documented information system to manage inventory and facilitate the process of borrowing and returning goods in the laboratory. The lack of such an information system can cause problems in inventory management and laboratory use. Therefore, a community service program was carried out to develop a free inventory feature integrated with digital signatures in the SIM-LAB application at the Department of Informatics and Computer Engineering, FT UNM. This program aims to improve the quality of inventory management in the laboratory. In order to solve the problems faced by partners, the solutions offered through this PKM program are 1) Implementing a free inventory feature integrated with digital signatures in the SIM-LAB JTIK application, 2) Provide training related to the application, use, and maintenance of free swollen features integrated with digital signatures to JTIK Laboratory operators. After being given training, they are then guided to apply the results of the training in order to improve the quality of inventory management in the laboratory.